NK Cell-Based Immune Checkpoint Inhibition - Khan, Muhammad; Arooj, Sumbal; Wang, Hua (Frontiers in Immunology, 2020)
Immunotherapy, with increasing therapeutic dimensions, is becoming an important mode of treatment for cancer patients. Inhibition of Immune checkpoints, which are the source of immune escape for various cancers, in one such immunotherapeutic dimension that has mainly been aimed at T cell in the past, is now seeing NK cell as new emerging target. Simultaneously, number of these checkpoints identified have also been increased in recent times. In addition to classical NK cell receptors, KIRs, LIRs and NKG2A, several other immune checkpoints have also been unraveled to cause dysfunction of NK cell in various cancers and chronic infections. These checkpoints including the revolutionized CTLA-4, PD-1 and recently identified B7-H3, as well as LAG-3, TIGIT & CD96, Tim-3, and most recently acknowledged checkpoints-members of the Siglecs family (SIglec-7/9), CD200 and CD47. An interesting dimension of the immune checkpoints is its candidacy for dual checkpoint inhibition resulting in therapeutic synergism. Furthermore, its combination with other forms of NK cell cytotoxicity restoration strategies could also strengthen its efficacy as an antitumor therapy. Here, we have undertaken a comprehensive review of the literature to date regarding NK cell based immune checkpoints.